Efek Self-Regulation Terhadap Fear of Missing Out Melalui Variabel Mediasi Self-Esteem Pada Siswa - Zainul Majdi; Sulma Mafirja; Suhaili (Universitas Islam Negeri Madura, 2024)
Fear of missing out, which is defined fear of losing valuable moments of another individual or group where the individual cannot be present and is marked by the desire to remain connected to what others are doing over the Internet. The factors that influence the level of fear are self-regulation and self-esteem. The aim of the study was to find out the effects of self-regulation on fear of being left behind through self-esteem mediation variables in students. This research uses quantitative with explanatory correlation types. This research has one independent variable, namely self-regulation, one mediator variable that is self-esteem, and one dependent variable which is fear of loss. Subject picking using random sampling. Respondents in the study were 75 people. Data collection using 3 instruments; scale fear of missing out, scale self regulation and scale of self-esteem. Data analysis using analytical path based regression and mediation using bootstraping bias corrected with confidential intervals of 95%. Results of the study show that there is an effect of self - regulation on fear of Missing out through self - estiem mediation variables in students